Filipinowitan and Buddy System: Strategies for Enhancing Reading Comprehension Among Grade 5 Learners - Jael, Elaine Jane; Mangindra, Anesa (International Journal of Arts, Sciences and Education, 2025)
In the ongoing pursuit of improving young learners' reading abilities, identifying effective instructional strategies is crucial. This study examines the impact of the Buddy System and Filipinowitan approaches in assessing the reading comprehension proficiency of Grade 5 students at H.N. Cahilsot Central Elementary School II during the first quarter of the 2022-2023 academic year. The researcher evaluates students' reading comprehension levels using Phil-IRI as a key assessment tool. A quasi-experimental research design was employed to measure the mean gain scores between pre-test and post-test results. Two groups—the experimental and control groups—played vital roles in this study. The experimental group received instruction through the Buddy System and Filipinowitan strategies, whereas the control group adhered to conventional reading instruction methods. Statistical analyses were applied to the collected data, serving as the foundation for the study’s evaluation.The results indicated that the intervention methods—Buddy System and Filipinowitan—were effective in improving reading comprehension. Pre-test findings demonstrated that both groups exhibited comparable comprehension levels before the implementation of the intervention. However, in the post-test, the experimental group achieved higher scores and demonstrated a more advanced level of reading comprehension than the control group.